ANALISIS TINGKAT KESEHATAN BANK DENGAN METODE RISK BASED BANK RATING PERIODE 2018-2022 (STUDI KASUS PT BANK NEO COMMERCE TBK) - Melisa Ayu Lestari (2023)
The purpose of this final project is to assess the health level of PT Bank Neo Commerce using the Risk Based Bank Rating (RBBR) method, utilizing four factors: Risk Profile, Good Corporate Governance, Earnings, and Capital. The writing method employed is quantitative descriptive. The data used is secondary data sourced from Financial Statements and Annual Reports from the past five years, specifically from 2018 to 2022. Data collection was conducted through documentation and literature review methods. The results of this study indicate that the overall health level of PT Bank Neo Commerce during the period of 2018-2022, based on the measurement of Non-Performing Loans (NPL) for Credit Risk falls under the "Adequate" composite. The measurement of Loan to Deposit Ratio (LDR) for Liquidity Risk falls under the "Healthy" composite. The assessment of Good Corporate Governance (GCG) based on the composite GCG rating through Self Assessment indicates a "Healthy" composite. The measurement of Net Interest Margin (NIM) for Profitability falls under the "Very Healthy" composite. Lastly, the measurement of Capital Adequacy Ratio for Capital falls under the "Very Healthy" composite.